DOUBLE SHEAR DESIGN TO REDUCED STAMPING FORCE - Arief, Rudi Kurniawan (TURBO [Tulisan Riset Berbasis Online], 2017)
Ideally processing of part using stamping machine using only 70-80 % of available force to keep machine in good shape for a long periods. But in some certain case the force may equal to or exceed the available maximum force so the company must sent the process to another outsource company. A case found in a metal stamping company where a final product consist of 3 parts to assembly with one part exceeded the force of available machine. This part can only process in a 1000 tons machine while this company only have 2 of this machine with full workload. Sending this parts outsource will induce delivery problems because other parts are processed, assembled and paint inhouse, this also need additional transportation cost and extra supervision to ensure the quality and delivery schedule. The only exit action of this problem is by reducing the force tonnage. This paper using punch inclining method to reduce the force. The incline punch will distributed the force along the inclined surface that reduce stamping force as well. Inclined surface of punch also cause another major problems that the product becoming curved after process. This problems solved with additional flattening process that add more process cost but better than to outsource the process. Chisel type of inclining punch tip was choosen to avoid worst deformation of product. This paper will give the scientific recomendation to the company.